Flow Channeling And Restriction Zone Identification in Gas Mask Filter Cartridges using CFD - Halif, M. Hazimuddin; Azmir, Nor Azali (International Journal of Integrated Engineering, 2025)
Gas mask filters are critical for protecting against hazardous gases and airborne pollutants, yet their performance is strongly influenced by internal airflow behavior. In this study, Computational Fluid Dynamics (CFD) was employed to investigate pressure drop, velocity distribution, and air age (residence time) within a gas mask cartridge. The simulations revealed a maximum pressure drop of 41.94 Pa, well within acceptable breathing resistance limits, but with non-uniform distribution across the absorbent bed. Velocity contours showed flow channeling forming near the inlet and outlet, leaving regions further from the outlet underutilized. Air age analysis confirmed these patterns, with some regions achieving the required 0.67–0.80 s contact time for effective adsorption, while others fell below this threshold. Under humid conditions, resistance increased, leading to longer residence times but reduced overall airflow renewal. These findings highlight that both cartridge can affect airflow uniformity, adsorption efficiency, and sorbent utilization. The findings can guide the optimization of filter design in achieve more balanced flow distribution and improved performance.